Response of native accessions of Stylosanthes guianensis to inoculation with rhizobia - Xavier, Deise Ferreira; Souto, Sebastião Manhães; Carvalho, Margarida Mesquita; Franco, Avílio Antonio (Pesquisa Agropecuaria Brasileira, 2014)
A pot trial was carried out in a glasshouse to verify Bradyrhizobium requirements for native accessions of Stylosanthes guianensis using an oxisol, with the following treatments; a) Five S. guianensis accessions: IPF 392/75, IPF 394/75, BAG 24, IPF 386/77; IPF 388/75; b) Two Bradyrhizobium sp strains: CB 756 and CIAT 527; a control either with or without nitrogen; e) Two fertility levels: (1) 25 mg P,kg-1 of soil and 30 mg K.Kg-1 of soil; (II) 50 mg P.kg-1 of soil and 60 mg K.kg-1 of soil, and 3 ton. Of lime. ha-1 and micronutrients. The results indicated that the native strains of Bradyrhizobium were effective in increasing nodulation, total N and dry weight of tops of the five S. guianensis accessions. In addition, the higher level of fertilizer application had a positive effect on growth of the S. guianensis accessions.